The Frenectomy Combined with the Free Gingival Graft: A Case Report - ขัดเงางาม รมณีย์ (Journal of Health Science of Thailand, 2021)
A frenum becomes a problem if the attachment is too close to the marginal gingiva. Tension on the frenum may pull the gingival margin away from the tooth. This condition is capable of plaque accumulation, creating diastemas, and limiting lip movement. When frenum is present, the traditional frenectomy alone generally is successful. However, when the frenulum is extensive, the possibility of coronal reformation exists. Several procedures have combined the frenectomy with either a laterally positioned flaps when esthetic concerns or free gingival graft has taken from the palate. A case report demonstrated the continued efficacy of the traditional palatal free gingival graft when the patient had an extensive frenulum, inadequate attached gingiva and an area of minimal esthetic concerns was involved. This combination procedure eliminates excessive pull on the gingiva, ensures decrease more gingival recession and creation of an adequate attached gingival barrier.